APLIKASI MOBILE KONSULTASI DOKTER DENGAN MENGGUNAKAN FRAMEWORK REACT NATIVE DI KLINIK MITRA ANDA TIMIKA - Bagus Rahmatoko; Ninik Haryani; Moh Rofi (LPPM Politeknik Saint Paul Sorong, 2023)
Today's society often complains about various ailments that are felt. By consulting directly or face to face, the community can complain about various things that are felt. However, consultations are often carried out face-to-face with doctors or health professionals who often complain about the time and schedule of examinations by doctors. By using a face-to-face system it is felt to be less effective for the community. To address these issues, the authors created Doctor Consultation apps for Android and iOS, constructed them with the React Native framework, and leveraged services from the Firebase Firestore Database as the system's database, Firebase Authentication as authentication to access the system. Firebase Storage for data storage. Mitra Anda App includes consulting features, doctor information based on previous user ratings, news and offers from clinics, authentication that checks user authorization to access the system, get clinic directions, etc. Mitra Anda application will make it simpler for the general public to conduct consultations or obtain medical services from doctors, find out the location of clinics, receive health news and offers from clinics to receive health services directly.